Rainbow Valley [Dúhové údolie anglicky] / book 7 - Montgomery, Lucy Maud, 1874-1942 (Anne of Green Gables - The complete collection, 2022)
There was a little unfailing spring, always icy cold and crystal pure, in a certain birch-screened hollow of Rainbow Valley in the lower corner near the marsh.